The power of identification schemes - Kurosawa, Kaoru; Heng, Swee Huay (Springer, 2006)
In this paper, we show that identification schemes (ID-schemes) are very powerful in some areas of cryptography. We first prove an equivalence between non-interactive trapdoor commitment schemes and a natural class of identification schemes. We next propose a more efficient on-line/off-line signature transformation than Shamir-Tauman. As an application, we present a variant of Boneh-Boyen (BB) signature scheme which is not only on-line/off-line but also has a smaller public key size than the original BB scheme. Finally, we present the first identity-based ID-scheme which is secure against concurrent man-in-the-middle attack without random oracles by using our variant of BB signature scheme.